2022
DOI: 10.3390/foods11020170
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum subsp. plantarum and Fructooligosaccharides Combination Inhibits the Growth, Adhesion, Invasion, and Virulence of Listeria monocytogenes

Abstract: Listeria monocytogenes is a foodborne pathogen responsible for many food outbreaks worldwide. This study aimed to investigate the single and combined effect of fructooligosaccharides (FOS) and Lactiplantibacillus plantarum subsp. plantarum CICC 6257 (L. plantarum) on the growth, adhesion, invasion, and virulence of gene expressions of Listeria monocytogenes 19112 serotype 4b (L. monocytogenes). Results showed that L. plantarum combined with 2% and 4% (w/v) FOS significantly (p < 0.05) inhibited the growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 79 publications
0
1
1
Order By: Relevance
“…Contrary to our findings, FOS structures have been shown to prevent the adhesion of E. coli, Clostridium difficile , Bacteroides and Listeria monocytogenes to intestinal epithelial cells in vitro [ 54 , 55 , 56 , 57 ]. Since these studies show that the adhesion of both Gram-positive and Gram-negative bacteria can be inhibited, the lack of anti-adhesive effects of FOS in our MP cultures does not seem to be due to restriction to a certain bacteria class.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our findings, FOS structures have been shown to prevent the adhesion of E. coli, Clostridium difficile , Bacteroides and Listeria monocytogenes to intestinal epithelial cells in vitro [ 54 , 55 , 56 , 57 ]. Since these studies show that the adhesion of both Gram-positive and Gram-negative bacteria can be inhibited, the lack of anti-adhesive effects of FOS in our MP cultures does not seem to be due to restriction to a certain bacteria class.…”
Section: Discussioncontrasting
confidence: 99%
“…The most commonly used were probiotic-based biological control methods, in which probiotics inhibited LM by producing antibacterial substances (bacteriocins, organic acids, hydrogen peroxide) and nutritional competition. For example, Dong et al reported a combination of oligofructose and Lactiplantibacillus plantarum subsp. plantarum to achieve inhibition of the growth and adhesion of LM .…”
Section: Introductionmentioning
confidence: 99%